MODEL USAHATANI TERPADU SAYURAN ORGANIK-HEWAN TERNAK (Studi Kasus: Gapoktan Pandan Wangi, Desa Karehkel, Kecamatan Leuwiliang, Kabupaten Bogor, Provinsi Jawa Barat) - Firza Maudi; Nunung Kusnadi (Forum Agribisnis, 2011)
Agriculture sector in developing country, including Indonesia, faces many problems such as scarcity in productive agriculture land and continuous increase of demand for food.  Karehkel Village - West Java plans to develop integrated farming system (IFS) to address this issues.  The farming system at Karehkel Village integrates organic vegetables, livestock, and produces organic fertilizer and manure.   The purpose of this research is to develop quantitative model of IFS at Desa Karehkel and to determine the economic benefit IFS.  Using the Linear Programming model the optimal solution shows that the farm profit of IFS is higher than the Non-IFS.  The maximum profit can be reached by integrating organic vegetables – waste vegetables – livestock – manure – organic fertilizer (Bokashi).  The optimal solution also indicated that the whole organic fertilizer product  should be sold to the market since the cost per unit of organic fertilizer was relatively high.  Imposing  the organic fertilizer as the  input of organic vegetables farming reduced IFS total profit.